EDUKASI DAN DEMONSTRASI PEMBUATAN NUGGET IKAN, SINGKONG, DAN DAUN KELOR DALAM UPAYA PENCEGAHAN MASALAH GIZI PADA BALITA DI DAERAH PESISIR BARANGKA KABUPATEN BUTON - Sista; Bunga Sarmila; Rezky Saputri; Amriya Amriya; Asniati Asniati; Nur Ilani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Nutritional problems among toddlers remain a significant public health issue in Indonesia, particularly in coastal areas where the utilization of nutritious local food resources is still limited. One effort to prevent nutritional problems can be carried out through nutrition education and demonstrations of processing local food ingredients into healthy and attractive foods for toddlers. This study aimed to determine the effect of education and demonstrations on making nuggets made from fish, cassava, and moringa leaves in improving the knowledge and skills of mothers with toddlers regarding the utilization of local food as an effort to prevent nutritional problems among toddlers in the coastal area of Barangka, Buton Regency. This study used a descriptive method with a community service approach. The activity was conducted in Barangka Village, Kapontori District, Buton Regency, in 2026 with a sample of 18 participants consisting of mothers with toddlers and posyandu cadres selected using purposive sampling techniques. The activities were carried out through nutrition education, demonstrations of making nuggets from local ingredients, and evaluations using pre-test and post-test questionnaires. The results showed an increase in participants’ knowledge after the intervention. Before the activity, participants in the poor knowledge category were 50.0%, sufficient category 33.3%, and good category 16.7%. After the education and demonstration activities, the poor category decreased to 0%, the sufficient category increased to 55.6%, and the good category increased to 44.4%. These findings indicate that education and demonstrations on processing local food ingredients are effective in improving community knowledge and skills regarding the utilization of nutritious local food to prevent nutritional problems among toddlers.